IMPLEMENTING SNOWBALL THROWING TECHNIQUE TO ENHANCE THE ELEVENTH GRADE STUDENTS’ SPEAKING SKILL AT SMA N.2 SIBORONG BORONG IN THE ACADEMIC YEAR OF 2023/2024 - Silaban, Regina Rona; Raja, Viator Lumban; Sembiring, Novalina (NextGen Education Review Journal, 2024)
This study aims to investigate the potential impact of employing the Snowball Throwing technique to enhance students’ speaking skill. By examining the reactions and feedback from students who have undergone instruction using this technique, valuable insights can be gained into its efficacy in bolstering speaking acquisition. The findings hold significance for researchers seeking innovative approaches to enhance language learning. This research is Classroom Action Research (CAR). The research findings showed that teaching speaking skill by using Snowball Throwing technique to the eleventh grade students of SMA N. 2 Siborong borong could improve their speaking ability. It is advisable that English teachers try applying Snowball Throwing technique in teaching speaking skill.Quantitative data analysis shows an increase in the average score of 0 in the Pre-test with 0% of students scoring ≥ 75, in the Formative-test 5 with 14,28% of students scoring ≥75, and 27 in the Post-test with 77,12% of students got a value of ≥75. Then the results of this study increased. This research was carried out in SMA N. 2 Siborong borong to the eleventh grade students in the academic Year 2022/2023 that this research was successfully carried out at SMA N. 2 Siborong borong and it can be proven from the results of increasing student achievement from the pre-test to the formative-test to the post-test. The results of this study are expected to provide valuable information on how to improve students' speaking skil by applying the Snowball Throwing technique. During the research the writer knows that in order to improve speaking skills students must create an interesting technique for students, so that students are interested in learning.